Asymptotic normality of the local linear estimation of the conditional density for functional dependent and censored data - Benkhaled, Abdelkader; Madani, Fethi; Khardani, Salah (South African Statistical Journal, 2020)
In this paper,we study the asymptotic behaviour of the nonparametric local linear estimation of the conditional density when the interest variable is subject to random right censoring of the scalar response variable given a functional random covariate taking values in a semi-metric space. Under some regularity conditions, the joint asymptotic normality of the estimators of the conditional density is established.